2018
DOI: 10.1007/s13361-018-2044-5
|View full text |Cite
|
Sign up to set email alerts
|

Disambiguation of Isomeric Procyanidins with Cyclic B-Type and Non-cyclic A-Type Structures from Wine and Peanut Skin with HPLC-HDX-HRMS/MS

Abstract: Hydrogen/deuterium exchange coupled with high-resolution mass spectrometry was successfully applied for the identification of A-type tetrameric, pentameric, and hexameric procyanidins in peanut skin. This extended a previous study on isomeric cyclic B-type unconventional tetramer, pentamer, and hexamer procyanidins found in wine and cranberries. Not only had the method successfully identified the procyanidins with a single A-linkage (e.g., tetrameric m/z 1153.2608) by means of distinguishing them from their is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 19 publications
4
31
1
Order By: Relevance
“…As previously seen by Longo et al here too, the c‐analogs appear to retain those features that distinguished them from their linear analogs, namely (a) the anticipated retention times and (b) the lower number of peaks (even just one). It was already reported that the increased polarity, a lower fragmentation probability (along with all the differences in the fragmentation patterns) and fewer peaks (usually only a main one with much smaller traces at higher retention times) are features distinguishing the cyclic from their linear (a‐ or l‐) counterparts.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…As previously seen by Longo et al here too, the c‐analogs appear to retain those features that distinguished them from their linear analogs, namely (a) the anticipated retention times and (b) the lower number of peaks (even just one). It was already reported that the increased polarity, a lower fragmentation probability (along with all the differences in the fragmentation patterns) and fewer peaks (usually only a main one with much smaller traces at higher retention times) are features distinguishing the cyclic from their linear (a‐ or l‐) counterparts.…”
Section: Resultssupporting
confidence: 74%
“…The presence and distribution of cyclic B‐type proanthocyanidins containing (epi)gallocatechins (ie, prodelphinidins) in red and white wines have been demonstrated for the first time. Previous evidences of the relation between these cyclic oligomers and other factors (eg, winemaking procedures) were already shown for procyanidins . Overall, these two classes (cyclic B‐type procyanidins and cyclic B‐type prodelphinidins) showed similar behaviors under many respects: (1) the retention times were anticipated with respect to their linear analogs; (2) they showed much fewer HPLC peaks with respect to their linear analogs, indicating the presence of just one main regio‐ and stereoisomer; (3) the MS/MS spectra showed much less fragmentation with respect to their linear analogs (higher pseudo‐molecular ion intensity) at 15‐eV collision energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations